Features of hybridized AA7072 and AA7075 alloys nanomaterials with melting heat transfer past a movable cylinder with Thompson and Troian slip effect - Zaib, Aurang; Khan, Umair; Ishak, Anuar; Eldin, Sayed Mohamed; Alotaibi, Abeer M.; Raizah, Zehba; Waini, Iskandar; Elattar, Samia; Abed, Ahmed M. (Elsevier B.V., 2022)
A number of scientists have indicated interest in the promising area of research that involves improving heat transmission by utilizing nanoparticles. The dynamic properties of nanofluids reflect several applications in the cooling process, thermal engineering, heat exchangers, magnetic cell separation, energy production, hyperthermia, etc. In light of the appealing implications of nanofluids, the current research aims to explore the melting process of MHD hybrid AA7072 and AA7075 alloy nanoparticles from a movable cylinder. It also incorporates the irregular Thompson and Troian slip effect to simulate the intricate features of the nanofluid flow. The primary nonlinear partial differential equations (NPDEs) are converted into nonlinear ordinary differential equations (NODEs) with the use of the similarity technique. These converted equations are unraveled numerically via applying the built-in program bvp4c in MATLAB. It is visually examined that physical parameters affect the temperature and skin friction. The outcomes suggest that double solutions are found in a certain range of movable cylinder parameter. In addition, the skin friction is decelerated due to the critical shear rate and velocity slip factors while it is enhanced with the influence of suction and nanoparticles volume fraction. Moreover, the temperature is uplifted due to nanoparticles volume fraction and is declined due to Stefan number. In case of quanitative descriptions, the skin friction boosted up by almost 3.64% and 1.18% for the particular upper and lower branch outcomes due to the superior influences of nanoparticle volume fraction. Also, the skin friction decelerated for the branch of upper and lower solutions at about 5.26% and 22.55%, respectively, due to the larger velocity slip parameter.